Effect of Marinated Gelugur Acid (Garcinia atroviridis) on the Chemical and Organoleptic Quality of Rarit Beef - Maiza; Patriani, P; M.Silalahi (Jurnal Peternakan Integratif, 2023)
This study aims to determine the effect of using tamarind gelugur on the chemical and organoleptic quality of beef rarit. This research was conducted in September – December 2022 at the Research and Technology Laboratory, Faculty of Agriculture and Animal Production Laboratory, Faculty of Agriculture, Universitas Sumatera Utara. The design used in this study was Factorial RAL (Completely Randomized Design) with 4 treatments, namely factor 1, the concentration of gelugur acid (P0 = 0 ml, P1 = 30 ml, P2 = 60 ml, P3 = 90 ml) and factor 2, namely length of storage time (H1 = 4 days, H2 = 8 days) with 3 replications. The parameters used in this study were chemical quality tests, namely water content, fat content, and protein content and organoleptic tests, namely colour, scent, texture, and taste. The results showed that marinating beef using garcinia provides with a concentration of 30 ml, 60 ml, and 90 ml had a very significant effect on the chemical and organoleptic quality of garcinia atrovidis beef rarit with a storage time of 4 days at room temperature. The higher the concentration used, the better the chemical and organoleptic quality of the beef rarit.